LOSS OF PAVEMENT SUPPORTING CAPACITY DUE TO FROST ACTION AS MEASURED BY PLATE BEARING TESTS - Sayman,William C. (1955)
This paper presents a summary of field studies which have been made to determine the effect of frost action on the magnitude and duration of loss in pavement supporting capacity, measured by plate bearing tests, as part of a comprehensive frost investigational program initiated by the Corps of Engineers in 1944. The purpose of this program is to develop design and evaluation criteria for pavements constructed on subgrade soils subjected to frost action. (Author)